PENGARUH DZIKIR TERHADAP MENTAL EMOSIONAL BALITA - Susanty, Nurbiah Eka; Nurlina, Nurlina (Voice of Midwifery, 2022)
Growth and development in the preschool period is a strong foundation, which is very influential for further development. Healthy and good development will take place, if the social environment (school) facilities and children's potential can run well, one method that can be applied is the routine of dzikir. Purpose: To determine the effect of dzikir on emotional mentality in toddlers aged 3-5 years at Aisyiyah Barumbung Kindergarten. Methods: Quasi-experimental one group pretest-posttest design with a total sampling of 30 children aged 3-5 years in Aisyiyah Barumbung Kindergarten. The data was taken from the results of the pretest and posttest using KMME after being given the dzikir intervention for a month, with t-test analysis. Results: The average emotional mental score before receiving dzikir was 61.67 (SD=11.75). After getting dzikir, the average obtained is 93.53 (SD = 6.78). The results of the paired sample t-test showed that the tcount was 2.2e-16 (p <0.05). Conclusion: there is an effect of dzikir on emotional mentality in toddlers aged 3-5 years. Dzikir is expected to be routinely carried out every day, especially after the five daily prayers, before going to bed and when the toddler's emotional state is unstable. Keywords: Dzikir, Emotional mental, Toddler